Mastering the Ultimate High Ground: Next Steps in the Military Uses of Space - Lambeth, Benjamin S. (RAND Corporation, 2003)
Assesses the military space challenges facing the Air Force and the nation in light of the findings and recommendations of the Space Commission. The author reviews the Air Force's involvement in space since its creation as an independent service in 1947; examines the circumstances that occasioned the commission's creation and the conceptual and organizational roadblocks that have impeded a more rapid growth of U.S. military space capability; and enumerates the challenges facing the Air Force with respect to space.